Detection and identification of multiple IGBT open‐circuit faults in PWM inverters for AC machine drives. Issue 4 (1st April 2019) - Bae, Cheol‐Ju; Lee, Dong‐Choon; Nguyen, Thanh Hai
Abstract : This study proposes a new scheme for online detection and identification of single and multiple insulated‐gate bipolar transistor (IGBT) open‐circuit faults in three‐phase pulse‐width modulation (PWM) inverters of AC machine drives, which is based on Park's vector of machine phase currents. First, the switch open‐circuit faults are detected by monitoring dwell times of the vector of the actual phase currents expressed in the stationary reference frame in each sector, where the normalisation of the current to its reference value is utilised, by which the immunity to the false alarms in transient conditions is improved significantly. Then, the IGBT open‐circuit faults are identified, where leg open‐circuit conditions are in the first place determined based on the average values of the normalised line‐to‐line currents. Next, the single open‐circuit IGBT is located from the polarity of the corresponding phase current. By the proposed diagnosis method, the fault detection time is at the longest about 52.3 and 54% of a fundamental period in the simulation and experimental tests, respectively, and the 27 possible cases of IGBT open‐circuit faults combined for all IGBTs in the inverter can be identified. In addition, this algorithm can be implemented without any additional hardware and computational burden.